Strawberry Shortcake. The Glimmerberry ball movie - Zaslove, Mark.; Crocker, Carter; Magon, Jymn.; Hathcock, Bob.; Cummer, Anna.; Beurs, Karl.; Melbye, Lisa.; Whitewood, Chip.; Saunig, Ashley; Twentieth Century Fox Home Entertainment, Inc.; American Greetings Corporation; MoonScoop Group (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2010)
"Celebrate winter with Strawberry Shortcake and friends at the Glimmerberry Ball! It's a delightful, fun-filled time as the girls exchange presents, solve a hollow tree mystery, and set out to carve the most beautiful Glimmerberry lantern ever! Just like Strawberry says, 'The whole community will come together and work together and help each other, friends helping friends, during the long months of winter. That's the real meaning behind it!'"--Container.
Title from container.
"American Greetings"--Container.
"MoonScoop"--Credits.
Special features: "Never say never" sing-along, Read-along storybook, DVD-ROM printable coloring pages.
"Special features are not rated or close-captioned."--Container.
Story editors, Karl Beurs, Lisa Melbye ; theme, Chip Whitewood and Ashley Saunig.
Keywords: Strawberry Shortcake (Fictitious character) -- Juvenile drama; Friendship -- Juvenile drama; Winter -- Juvenile drama; Strawberry Shortcake (Fictitious character) -- Juvenile films; Friendship -- Juvenile films; Winter -- Juvenile films; Friendship; Strawberry Shortcake (Fictitious character); Winter; Feature films; Children's films; Animated films; Video recordings for the hearing impaired; Fiction films; Animated films; Children's films; Drama; Feature films; Fiction films; Juvenile works; Motion pictures; Video recordings for the hearing impaired